2022
DOI: 10.3389/feart.2022.863357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Microbial Content on Engineering Characteristics of Improved Expansive Soil

Abstract: In order to study the influence of microbial content on the engineering properties of expansive soil im-proved by microbially induced calcium carbonate (MICP) method, and to clarify its influence law and mechanism of action, and to provide some theoretical reference for the application of MICP method to expansive soil treatment. Microbial reproduction and their mineralization in expansive soils have been studied. The problems such as moisture content controlling and low calcium content in the process of treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, actinomycetes have not played a role in improving the cohesion of expansive soils [174]. Microbially induced calcite precipitation (MICP) has attracted more attention as a new soil modification method, as the swelling-shrinkage, compressibility, hydrophilicity, and soil strength of expansive soils can be improved using this technology [176][177][178][179]. Nevertheless, research is still needed regarding the required nutrition of strains in engineering applications and the long-term effects of soil modification.…”
Section: Biological Modification Methodsmentioning
confidence: 99%
“…However, actinomycetes have not played a role in improving the cohesion of expansive soils [174]. Microbially induced calcite precipitation (MICP) has attracted more attention as a new soil modification method, as the swelling-shrinkage, compressibility, hydrophilicity, and soil strength of expansive soils can be improved using this technology [176][177][178][179]. Nevertheless, research is still needed regarding the required nutrition of strains in engineering applications and the long-term effects of soil modification.…”
Section: Biological Modification Methodsmentioning
confidence: 99%
“…The experimental study of using microorganisms to improve unfavorable soil makes it possible to apply this method to engineering. Scholars have used MICP technology to improve unfavorable soil to varying degrees, including sand [ 40 , 41 , 42 ], silt [ 43 , 44 , 45 ], loess [ 46 , 47 , 48 , 49 , 50 ], expansive soil [ 51 , 52 , 53 , 54 ], and mucky soil [ 55 , 56 ], using this method, and the unconfined compressive strength and cohesion of the soil are significantly improved, which can be used in engineering practice. In the field of geotechnical engineering, the research results of MICP on soil improvement can be used for foundation reinforcement [ 57 , 58 , 59 ], earth dam reinforcement [ 60 ], wind prevention, sand fixation [ 61 ], reservoir bottom anti-seepage, and anti-seepage curtains [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The carbonate ions combine with calcium ions in the soil to form calcium carbonate precipitates adsorbed on the surface of the bacteria (Liu et al, 2017). Relevant literature have shown that the MICP method can effectively reduce the expansion and contraction of expansive soils (Tiwari et al, 2021;Li et al, 2021) and improve their strength (Jiang et al, 2021;Ouyang et al, 2022). However, most of the studies on the improvement of expansive soils using the MICP method have focused on the physical properties, strength properties, and deformation properties of the improved expansive soils under short-term loading.…”
Section: Introductionmentioning
confidence: 99%